2010
DOI: 10.1002/esp.1995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different mass transport calculation methods for wind erosion quantification purposes

Abstract: Quantitative estimation of the material transported by the wind under fi eld conditions is essential for the study and control of wind erosion. A critical step of this calculation is the integration of the curve that relates the variation of the amount of the material carried by the wind with height. Several mathematical procedures have been proposed for this calculation, but results are scarce and controversial. One objective of this study was to assess the effi ciency of three mathematical models (a rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…(2) was used as a reference for comparisons with other equations. This result is according to the results obtained by Panebianco et al (2010) who found that the exponential equation is a very flexible and robust method to estimate the HMT in a loam sandy soil of the semiarid pampas.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…(2) was used as a reference for comparisons with other equations. This result is according to the results obtained by Panebianco et al (2010) who found that the exponential equation is a very flexible and robust method to estimate the HMT in a loam sandy soil of the semiarid pampas.…”
Section: Resultssupporting
confidence: 92%
“…(5), probably because the integration heights were different in each study: Buschiazzo and Zobeck (2005) integrated from the soil surface compared from 12.5 cm in this study. In a loamy-sand soil of the semiarid Pampas the use of different sampling arrangements and different mass flux models has produced differences of more than 45% in mass transport estimates, even under similar field conditions (Panebianco et al, 2010). HMT calculated with different equations correlated significantly (p b 0.01 Table 5) but the slope of the regression equation was not 1.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering the BSNE efficiency3233 range and the limitations of the methodology34 discussed in the methods section, the values presented here could be underestimated by up to around 50%, especially at the plane and the convex areas. However, the main reason for the underestimation in that case was due to the fact that the distribution of the mass flux across height was exponential, which is not the case in most of the datasets observed herein, especially during the periods of greater mass fluxes (Fig.…”
Section: Resultsmentioning
confidence: 84%